新型冠状病毒感染后以Balint综合征为首发 表现的克⁃雅病一例. - 叶雯露; 庄圣; 徐加平; 李洁; 黄译腺 (Chinese Journal of Contemporary Neurology & Neurosurgery, 2026)
Objective To report the clinical diagnosis and treatment of a case of sporadic Creutzfeldt - Jakob disease (sCJD), Heidenhain variant, presenting initially with Balint syndrome following severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection, and to review relevant literature to summarize the clinical characteristics of this disease. Methods and Results An 81-year-old male patient was admitted to The Second Affiliated Hospital of Soochow University on August 19, 2023, with clinical manifestations of gait instability, simultanagnosia, optic ataxia, and oculomotor apraxia (Balint syndrome). The condition progressively worsened, with the development of dementia, features of cerebellar involvement, and myoclonus. Cerebrospinal fluid tested positive for 14 - 3 - 3γ protein. DWI showed cortical hyperintensities in the bilateral parieto-occipito- temporal lobes, displaying the "cortical ribbon sign". EEG revealed frequent medium-to-high amplitude slow waves predominantly in the fronto-temporal region. The final diagnosis was sCJD, Heidenhain variant, presenting initially with Balint syndrome. Treatment aimed at improving cognition and controlling myoclonus yielded a poor response. Twenty days after discharge, the patient developed akinetic mutism and dyspnea, ultimately succumbing to respiratory failure. Conclusions Balint syndrome is a rare initial clinical manifestation of sCJD, warranting early recognition. SARS-CoV-2 infection may potentially trigger or accelerate the progression of sCJD.